PENGARUH PRAKTEK MANAJEMEN LABA DAN KINERJA KEUANGAN PERUSAHAAN TERHADAP PENETAPAN GOOD CORPORATE GOVERNANCE (GCG) (Studi Empiris pada Perusahaan yang Terdaftar dalam Corporate Governance Perception Index (CGPI) 2010) - ETIKA IRMA SUGIARTI (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2013)
The purpose of this research is to find the influence of earning management and financial performance to assembling GCG. Earning management in this research measure with discretionary accrual. Financial perform measure with Return on Asset (ROA), Return on Equity (ROE), and Tobin’s Q. GCG in this research has two variale, such as institutional ownership and managerial ownership. The sample of this study was companies listed in CGPI. The amount of the sample was 19 companies within three periods, such as 2009 until 2011. The data was collected using purposive sampling method. The result of this study that earning management doesn’t influence to GCG. ROE doesn’t influence to institutional ownership and managerial ownersip. Tobin’s Q signifikant influence to institutional ownership. ROA signifikant influece to managerial ownership.